STRATEGI KONTEN SOSIAL MEDIA DI SMA PGRI 2 DEPOK - Ahmad Hartadi; Ayu Suryani; Muhammad Anda Afriansyah (LAP4B, 2026)
This Community Service (PKM) activity was held at SMA PGRI 2 Depok with the aim of providing students with an understanding of the importance of social media content strategies for building a positive personal brand. The rapid growth of social media has made creating engaging and communicative content a crucial skill in the digital age. Through this activity, participants were educated on the concepts of personal branding, consumer loyalty, and effective content creation techniques for social media videos. The activity was implemented through material delivery, interactive discussions, case studies, and simple practices for creating content using effective social media strategies. The material covered an introduction to personal branding, the characteristics of engaging content, techniques for developing content flow that builds emotional connection with audiences, and utilizing social media platforms as a means of promotion and communication. The results of the activity demonstrated high enthusiasm among participants throughout the PKM. Students understood the concept of content strategy in social media and the importance of building emotional connections with audiences to enhance personal branding. With this PKM activity, it is hoped that SMA PGRI 2 Depok students can improve their digital literacy skills, creativity in creating content, and understand the importance of strategy in content creation as an effort to build positive personal branding in the digital era.